Pelatihan Desain Grafis Bagi Pemuda Karangtaruna Desa Tunggalroso, Kebumen, Jawa Tengah - Atmaja Septa Miyosa; Priya Wintar Yuhanto; Sugiyo Winoto; Suparna Suparna; Sarwanto Sarwanto (Jurnal Abdimas ADPI Sains dan Teknologi, 2022)
The publication design is a communication medium needed by the community of Tunggalroso village, Prembun, Kebumen, Central Java. Human resources in Tunggalroso village who have graphic design skills are still limited. The purpose of the activity is to improve the ability to create publication designs for participants. The method used is a scheduled learning method including lectures, discussions, Q&A, followed by practice. The training was held in the Tunggalroso Village Hall on 20 to 24 September 2021, attended by 15 participants. The results of the training varied including the publication of activities, social events, publications for institutions, posters for celebrating holidays. The evaluation shows that the design already has the feasibility to be published in the community, because it already has design qualities such as legibility of letters, selection of adequate color contrast, dynamic composition and mastery of the field. The conclusion is that graphic design training has a significant impact on improving the skills of creating publication designs for youth Karangtaruna in Tunggalroso village.